Protection against pressure overload-induced right heart failure by uncoupling protein 2 silencing. Issue 7 (8th March 2019) - Esfandiary, Azadeh; Kutsche, Hanna S; Schreckenberg, Rolf; Weber, Martin; Pak, Oleg; Kojonazarov, Baktybek; Sydykov, Akylbek; Hirschhäuser, Christine; Wolf, Annemarie; Haag, Daniela; Hecker, Matthias; Fink, Ludger; et al.
Abstract: Aims: The role of uncoupling protein 2 (UCP2) in cardiac adaptation to pressure overload remains unclear. In a classical model of left ventricular pressure overload genetic deletion of UCP2 (UCP2 −/− ) protected against cardiac hypertrophy and failure. However, in UCP2 −/− mice increased proliferation of pulmonary arterial smooth muscle cells induces mild pulmonary hypertension, right ventricular (RV) hypertrophy, and reduced cardiac output. This suggests a different role for UCP2 in RV and left ventricular adaptation to pressure overload. To clarify this situation in more detail UCP2 −/− and wild-type mice were exposed to pulmonary arterial banding (PAB). Methods and results: Mice were analysed (haemodynamics, morphometry, and echocardiography) 3 weeks after PAB or sham surgery. Myocytes and non-myocytes were isolated and analysed separately. Cell shortening of myocytes and fura-2 loading of cardiomyocytes were used to characterize their function. Brd assay was performed to study fibroblast proliferation. Isolated mitochondria were analysed to investigate the role of UCP2 for reactive oxygen species (ROS) production. UCP2 mRNA was 2.7-fold stronger expressed in RV myocytes than in left ventricular myocytes and stronger expressed in non-myocytes compared with myocytes. Three weeks after PAB, cardiac output was reduced in wild type but preserved in UCP2 −/− mice. UCP2 −/− had increased RV wall thickness, but lower RV internal diameters and displayed a significant stronger fibrosis. Cardiac fibroblasts from UCP2 −/− had reduced proliferation rates but higher collagen-1 expression. Myocytes isolated from mice after PAB banding showed preserved function that was further improved by UCP2 −/− . Mitochondrial ROS production and respiration was similar between UCP2 −/− or wild-type hearts. Conclusion: Despite a mild pulmonary hypertension in UCP2 −/− mice, hearts from these mice are well preserved against additional pressure overload (severe pulmonary hypertension). This—at least in part—depends on different behaviour of non-myocytes (fibroblasts).